Injectable cell-encapsulating composite alginate-collagen platform with inducible termination switch for safer ocular drug delivery. (May 2019) - Wong, Francisca Siu Yin; Tsang, Ken Kin; Chu, Amy Man Wah; Chan, Barbara Pui; Yao, Kwok Ming; Lo, Amy Cheuk Yin
Abstract: Effective retinal drug delivery remains a challenge for treating vision-threatening diseases. Encapsulated-cell therapy (ECT) can provide local drug delivery without repeated invasive injections but is plagued by unsteady performance and biosafety issues. Here, an injectable composite alginate-collagen (CAC) ECT gel with a Tet-on inducible pro-caspase 8 mechanism that acted as an orally-inducible biosafety switch was developed for safer drug delivery. The optimised gels (2 mg/ml collagen, 1.5% high molecular weight alginate and 50, 000 cells/gel) could be effectively terminated in vitro (≥20 pg/ml Doxycycline) and in vivo (1 mg/ml oral Doxycycline after 48 h). Also, they displayed effective proliferation control and continuous delivery of bioactive glial-cell derived neurotrophic factor (GDNF) with no significant gel degradation in vitro and in rat vitreous. Most importantly, intravitreally injected gels demonstrated therapeutic efficacy in Royal College of Surgeons rats with degenerating retina in reducing photoreceptor apoptosis and retina function loss. Furthermore, double gel injections into the same eye yielded better outcomes without compromising gel viability. Retrieved gels showed no host-tissue attachment or cell-protrusion 6 months post-implantation. The CAC ECT system exhibited mechanical stability, good encapsulation power, cell viability support, multiplexed GDNF dosage, and compatibility with different cell types (HEK293 and ARPE-19) without immunosuppressant, making it an attractive, safe and well-controlled platform for treating various eye diseases.